THE EFFECT OF SALES PROMOTION ON PURCHASE DECISION TO USE INDIHOME PRODUCTS AT PLASA TELKOM NIAS - Zega, Oktorianus (Strategic Management Business Journal, 2025)
Research background: This study aims to determine the extent of the influence of sales promotion on the decision to use Indihome products at Plasa Telkom Nias. Purpose of the article: This study provides practical implications for Plasa Telkom Nias management to improve the quality and scope of promotions in order to attract and retain customers. The results showed that sales promotion had a significant influence on the decision to use Indihome products, with a significance value of 0.000 <0.05. This means that the better the sales promotion strategy carried out, the higher the likelihood of customers deciding to use Indihome products. Methods: The study used a quantitative method with a survey approach to 57 Indihome customers selected purposively. The data analysis technique used simple linear regression and determination coefficient test.